Lavellodrilus notosetosus sp. nov. (Annelida, Crassiclitellata, Acanthodrilidae): a new Mexican earthworm with uncommon characters, revealed by a preliminary revision of subfamily Acanthodrilinae - Fragoso, Carlos; Rojas, Patricia (Zootaxa, 2016)
A new acanthodriline earthworm species, Lavellodrilus notosetosus sp. nov., is described from tropical rain forests of southern Mexico. The new species is placed within the genus Lavellodrilus by the presence of mesial spermathecal pores. It is separated from other species of the genus by the dorsal location of setae cd in most of the body, last hearts in segment 13, first intestinal segment in 20 and genital setae in segment 12. A preliminary morphological revision of all genera and species of Acanthodrilinae was undertaken in order to: i) evaluate if the mesial spermathecal pores justify the status of Lavellodrilus, ii) determine how common (expressed as percentages of species having the character) the diagnostic characters of the new species are in the subfamily, iii) clarify if these characters exhibit a geographical pattern, and iv) contribute towards a comprehensive analysis of the Acanthodrilinae. In this revision, species were separated in nine geographical regions: USA, northern Mexico, southern Mexico, Caribbean Islands (northern hemisphere), and South America, South Africa, Madagascar, Australia, New Zealand, New Caledonia and Antarctic Islands (southern hemisphere). As a result of the revision it was found that among the 511 recognized species of Acanthodrilinae only 11 species have a mesial location of the spermathecal pores, in two cases probably representing monophyletic groups (Lavellodrilus and a group of South African Parachilota species). It was also found that the distinguishing characters in L. notosetosus sp. nov., notably the location of last hearts, genital setae and the first intestinal segment, are uncommon characters in the acanthodriline earthworm fauna of southern Mexico and Central America, but more frequent in North America, the Caribbean, and the southern hemisphere. We conclude that the acanthodrilines from the northern hemisphere are morphologically more similar to those from Australia, New Zealand, and New Caledonia than to those of South Africa and South America.